Determinan Struktur Modal Dalam PerspektifPecking Order Theory dan AgencyTheory (Studi Empiris Pada Perusahaan Manufaktur yang Listing di BEI Tahun 2010-2013) - Sigita Lestari (Universitas Negeri Padang, 2015)
This study aims to determine the determinants of capital structure in perspective pecking order theory and agency theory. Where this research analyze the variable profitability, company size, business risk in the pecking order theory perspective and variable growth opportunity and managerial ownership in the perspective of agency theory. The population in this study were all manufacturing companies listed on the stock exchanges of Indonesia from 2010 - 2013. The study sample as many as 336 (84 companies sample multiplied by 4 years of observation). The analytical method used is the classical assumption, multiple regression analysis, model test and descriptive statistics. The results showed that the variables of profitability in the pecking order theory perspective a significant negative effect on the capital structure while variable size and variable business risks in perspective pecking order theory has no effect on the capital structure. Variable growth opportunity in the perspective of agency theory a significant positive effect on the capital strukture while variable managerial ownership has no effect on the capitalstructure.Keywords: pecking order theory, profitability, company size, business risk, agency theory, growth opportunity, managerial ownership, capitalstructure.